A comprehensive evaluation of adaptive daily planning for cervical cancer HDR brachytherapy. (8th November 2016) - Meerschaert, Rebecca; Nalichowski, Adrian; Burmeister, Jay; Paul, Arun; Miller, Steven; Hu, Zhenghui; Zhuang, Ling
Abstract : The purpose of this study was to evaluate adaptive daily planning for cervical cancer patients who underwent high‐dose‐rate intracavitary brachytherapy (HDR‐BT) using comprehensive interfractional organ motion measurements. This study included 22 cervical cancer patients who underwent 5 fractions of HDR‐BT. Regions of interest (ROIs) including high‐risk clinical tumor volume (HR‐CTV) and organs at risk (OARs) were manually contoured on daily CT images. All patients were clinically treated with adaptive daily plans (ADP), which involved ROI delineation and dose optimization at each treatment fraction. Single treatment plans (SP) were retrospectively generated by applying the first treatment fraction's dwell times adjusted for decay and dwell positions of the applicator to subsequent treatment fractions. Various existing similarity metrics were calculated for the ROIs to quantify interfractional organ variations. A novel similarity (JRARM) score was established, which combined both volumetric overlap metrics (DSC, JSC, and RVD) and distance metrics (ASD, MSD, and RMSD). Linear regression was performed to determine a relationship between interfractional organ variations of various similarity metrics and D 2 cc variations from both plans. Wilcoxon signed‐rank tests were used to assess ADP and SP by comparing EQD 2 D 2 cc ( α / β = 3 ) for OARs. For interfractional organ variations, the sigmoid demonstrated the greatest variations based on the JRARM, DSC, and RMSD metrics. Comparisons between paired ROIs showed differences in metrics at each treatment fraction. RVD, MSD, and RMSD were found to be significantly correlated to D 2 cc variations for bladder and sigmoid. The comparison between plans found ADP provided lower EQD2 D 2 cc of OARs than SP. Specifically, the sigmoid demonstrated statistically significant dose variations ( p = 0.015 ). Substantial interfractional organ motion occurs during HDR‐BT based on comprehensive measurements and may significantly affect D 2 cc of OARs. Adaptive daily planning provides improved dose sparing for OARs compared to single planning with the extent of sparing being different among OARs. PACS number(s): 87.55.D, 87.55.de, 87.55.kh, 87.57.nj